Feasibility of the EORTC/NCIC Trial Protocol in a Neurosurgical Outpatient Unit: The Case for Neurosurgical Neuro-Oncology - Rapp, Marion; Sadat, Hosai; Slotty, Philipp Joerg; Steiger, Hans Jakob; Budach, Wilfried; Sabel, Michael (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Objective With the publication of the European Organization for Research and Treatment of Cancer/National Cancer Information Center (EORTC/NCIC) trial, concomitant radiochemotherapy followed by intermittent chemotherapy became the new treatment standard for patients with primary glioblastoma. Eight years after widespread introduction of this protocol, it is of interest to investigate whether this new standard has been established in daily neuro-oncologic practice. We were particularly interested in its practicality within a neurosurgical neuro-oncologic setting.Patients and Methods We analyzed primary glioblastoma patients diagnosed between 2005 and 2013 treated at our center according to the EORTC/NCIC trial. Parameters associated with treatment performance (interruption of radiotherapy, concomitant chemotherapy and intermittent chemotherapy, total number of cycles, and side effects) were retrospectively analyzed and compared with the available data from the EORTC/NCIC trial.Results In this single-center retrospective study, we identified 189 patients (116 men, 73 women; median age: 62 years) who were treated according to the EORTC/NCIC trial protocol. A total of 176 patients received cytoreductive surgery; 13 patients had stereotactic biopsy only (EORTC/NCIC trial: 239 patients and 48 patients, respectively). Radiotherapy had to be interrupted in 9 patients (5%) (EORTC/NCIC trial: 15 patients [5%]) and concomitant chemotherapy in 26 patients (14%) (EORTC/NCIC trial: 37 patients [13%]). In 156 patients (83%), adjuvant TMZ chemotherapy was initiated (6 median temozolomide [TMZ] cycles; range: 1–30). In the EORTC/NCIC trial, 223 patients (47%) received the intermittent chemotherapy protocol (median: 3 cycles; range: 1–7). Overall, 97 patients (62%) completed 6 TMZ cycles (EORTC/NCIC-trial: 105 patients [47%]); dose escalation to 200 mg/qm at the second cycle was performed in 91 patients (58%) (versus 149 patients [67%]). Intermittent TMZ therapy was discontinued in 59 patients (38%) (versus 118 patients [53%]). Median overall survival in our patient cohort was 19 months (versus 14.6 months); median time to progression was 9 months (versus 6.9 months).Conclusion Comparison between the feasibility of the treatment protocol established by the EORTC/NCIC trial (performed within the setting of a prospective randomized trial) and the daily routine in a dedicated neurosurgical neuro-oncologic department demonstrates that the protocol is suitable for daily practice within a neurosurgical unit.
Keywords: glioblastoma; temozolomide; concomitant radio chemotherapy